Altered Patterns of Functional Connectivity and Causal Connectivity in Salience Subnetwork of Subjective Cognitive Decline and Amnestic Mild Cognitive Impairment - Cai, Chunting; Huang, Chenxi; Yang, Chenhui; Lu, Haijie; Hong, Xin; Ren, Fujia; Hong, Dan; Ng, Eyk (Frontiers in Neuroscience, 2020)
The subjective cognitive decline (SCD) may last for decades priors to the onset of dementia, and has been proposed as a risk population for development to amnestic mild cognitive impairment (aMCI) and Alzheimer’s disease (AD). Disruptions of functional connectivity (FC) and causal connectivity (CC) in the salience network (SN) are generally perceived as prominent hallmarks of the preclinical AD. Nevertheless, the alterations in anterior SN (aSN) and posterior SN (pSN) remain unclear. Here, we hypothesized that both the FC and CC of the SN subnetworks, comprising of aSN and pSN, were distinct disruptive in the SCD and aMCI. We utilized resting-state functional magnetic resonance imaging (rs-fMRI) to investigate the altered FC and CC of the SN subnetworks in 28 healthy controls (HC), 23 SCD and 29 aMCI subjects. In terms of altered patterns of FC in SN subnetworks, aSN connected to the whole brain were significantly increased in the left orbital superior frontal gyrus (OSFG), left insula lobule (IL), right caudate lobule (CL), left rolandic operculum gyrus (ROG), while decreased FC were found in the left cerebellum superior lobule (CSL) and left middle temporal gyrus (MTG) when compared with the HC group. Notably, no prominent statistical differences were obtained in pSN. For altered patterns of CC in SN subnetworks, compared to the HC group, the aberrant connections in aMCI group were separately involved in the right cerebellum inferior lobule (CIL), right supplementary motor area (SMA) and left ROG, whereas SCD group exhibited more regions of aberrant connection, comprising of the right superior parietal lobule (SPL), right CIL, left inferior parietal lobule (IPL), left postcentral gyrus (PG), and right angular gyrus (AG). Specially, SCD group showed increased CC in the right CIL and left PG, whereas aMCI group showed decreased CC in the left precuneus (PreCU), corpus callosum (CCA) and right SMA when compared to SCD group. Collectively, our results suggest that analyzing the altered FC and CC observed in SN subnetworks, served as impressible neuroimaging biomarkers, may supply novel insights for designing preclinical interventions in the preclinical stages of AD.